Pengembangan Modul Bimbingan dan Konseling untuk Meningkatkan Kemampuan Komunikasi Interpersonal Siswa - Tuasikal, Jumadi Mori Salam; Mudjiran, Mudjiran; Nirwana, Herman (Konselor, 2016)
This research aims to formulate guidance and counseling module to improve interpersonal communication ability of students and to describe the level of applicability used by counselor. The method used was ADDIE model development. The properness test was done by three experts and the practicality test was done by three guidance and counseling teachers or counselors. The instruments used were skala likert, questionnaire and Focus Group Discussion (FGD). The data gathered in this research was analyzed by using descriptive statistic analysis and non-parametric statistic analysis. Â Based on these results, in general, it was concluded that the module developed was appropriate and could be used to help the students to improve their interpersonal